2013
DOI: 10.11607/jomi.3227
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Implantoplasty on Strength of the Implant-Abutment Complex

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(86 citation statements)
references
References 18 publications
2
76
0
3
Order By: Relevance
“…Implantoplasty did not affect significantly implant strength and resistance to fracture of wide diameter implants (i.e., 4.7 mm diameter; Chan et al, ). In contrast, variable results were reported for narrow/regular diameter implants (i.e., 3.75–4.1 mm diameter); in one study, a minimal reduction (i.e., 0.2 mm) in the core diameter of the implant did not significantly affect implant strength (Costa‐Berenguer et al, ), while average strength reduction of about 17%–40%—depending on implant platform/connection design—was observed in two other studies (Chan et al, ; Gehrke et al, ).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Implantoplasty did not affect significantly implant strength and resistance to fracture of wide diameter implants (i.e., 4.7 mm diameter; Chan et al, ). In contrast, variable results were reported for narrow/regular diameter implants (i.e., 3.75–4.1 mm diameter); in one study, a minimal reduction (i.e., 0.2 mm) in the core diameter of the implant did not significantly affect implant strength (Costa‐Berenguer et al, ), while average strength reduction of about 17%–40%—depending on implant platform/connection design—was observed in two other studies (Chan et al, ; Gehrke et al, ).…”
Section: Resultsmentioning
confidence: 94%
“…Kappa scores regarding agreement on the articles to be included in the full‐text analysis and those finally chosen were 0.91 and 0.95, respectively ( p < 0.001). Out of a total of 391 records assessed, 26 publications were finally included: six laboratory (Chan et al, ; Costa‐Berenguer et al, ; Gehrke, Aramburú Júnior, Dedavid, & Shibli, ; Sharon, Shapira, Wilensky, Abu‐Hatoum, & Smidt, ; de Souza Júnior et al, ; Tribst, Piva, Shibli, Borges, & Tango, ), two preclinical in vivo (Schwarz, Mihatovic, Golubovic, Becker, & Sager, ; Schwarz, Sahm, Mihatovic, Golubovic, & Becker, ), and 18 clinical publications (Englezos, Cosyn, Koole, Jacquet, & De Bruyn, ; Geremias et al, ; Matarasso et al, ; Nart, de Tapia, Pujol, Pascual, & Valles, ; Pommer et al, ; Ramanauskaite, Becker, Juodzbalys, & Schwarz, ; Romeo et al, ; Sapata, de Souza, Sukekava, Villar, & Neto, ; Schwarz et al, ; Schwarz, John, & Becker, ; Schwarz, John, Mainusch, Sahm, & Becker, ; Schwarz, John, Sahm, & Becker, ; Schwarz, John, Schmucker, Sahm, & Becker, ; Schwarz, Sahm, & Becker, ; Schwarz, Sahm, Iglhaut, et al, ; Suh, Simon, Jeon, Choi, & Kim, ; Thierbach & Eger, ). The two preclinical in vivo publications (Schwarz, Mihatovic, et al, ; Schwarz, Sahm, Mihatovic, et al, ) and the clinical of Romeo et al () and Romeo et al () publications reported on different aspects basically of the same study population.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies are inconclusive about the reduction 16 or not 9 of the implant's resistance by implantoplasty when 5 mm of the implant are exposed. In the present study, we observed that implantoplasty increases stress concentration on the implant and screw, indicating that the critical stress point of the material will be achieved earlier, thus leading to treatment failure.…”
Section: Discussionmentioning
confidence: 98%
“…3 However, it reduces the diameter and the wall thickness of the implant, 9 therefore the reliability of this treatment is still undefined.…”
Section: Declaration Of Interestsmentioning
confidence: 99%
“…Despite the promising results reported here and in other studies that evaluated the success of implantoplasty in the treatment of peri‐implantitis, 8,9,11,12 one cannot ensure that these implants will remain free of biologic and/or mechanical complications in the future. Indeed, information emerging from a recent in vitro study demonstrated that implantoplasty weakens the fracture strength of narrow implants 17 . Such reduced fracture strength is likely to be caused by reductions in implant diameter and thickness of implant walls after implantoplasty 18,19 .…”
Section: Discussionmentioning
confidence: 99%